2009
DOI: 10.5194/hessd-6-7213-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accessible integration of agriculture, groundwater, and economic models using the Open Modeling Interface (OpenMI): methodology and initial results

Abstract: Policy for water resources impacts not only hydrological processes, but the closely intertwined economic and social processes dependent on them. Understanding these process interactions across domains is an important step in establishing effective and sustainable policy. Multidisciplinary integrated models can provide insight to inform this understanding, though the extent of software development necessary is often prohibitive, particularly for small teams of researchers. Thus there is a need for practical met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…For example, Elag et al (2011) assessed the mass-balance errors of a hypothetical coupling scenario involving the coupling of simplified solute transport models including a surface and a sediment media model that were temporally misaligned. Bulatewicz et al (2010) successfully coupled agricultural, groundwater, and economic models to evaluate the impacts of alternative water use policies for a major aquifer in the US. Goodall et al (2011) and Castronova et al (2013) demonstrated the service-oriented modeling paradigm, where remote models were coupled using web-services technologies like the OGC's Web Processing Service (WPS) protocol.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Elag et al (2011) assessed the mass-balance errors of a hypothetical coupling scenario involving the coupling of simplified solute transport models including a surface and a sediment media model that were temporally misaligned. Bulatewicz et al (2010) successfully coupled agricultural, groundwater, and economic models to evaluate the impacts of alternative water use policies for a major aquifer in the US. Goodall et al (2011) and Castronova et al (2013) demonstrated the service-oriented modeling paradigm, where remote models were coupled using web-services technologies like the OGC's Web Processing Service (WPS) protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Esta necesidad de integración también ha fomentado que surjan conceptos asimilables al de repositorio de modelos. Pero en esta ocasión la idea de repositorio de modelos se orienta más hacia el desarrollo de software específico que sea capaz de acoplar o interconectar diversos modelos adecuadamente documentados (Bulatewicz et al 2009, Castronova et al 2013) que además tengan en cuenta la existencia de versiones en los modelos (Thornton et al 2005). No se trata tanto de tener una base de datos donde los investigadores busquen, ejecuten o descarguen modelos concretos, sino de una aplicación que permita encadenar la ejecución de distintos modelos modulares gracias a la existencia de los conectores adecuados.…”
Section: Documentación De Modelos En Distintas Disciplinas Científicasunclassified
“…Model-linking for subsystem models is a straightforward strategy that has been popularly used to resolve practical engineering cases (Argent 2004;Bulatewicz et al 2010;Castronova & Goodall 2010). However, in addition to the technical problems of model-linking, its ability to correct physical operations has also been a big challenge.…”
Section: Introductionmentioning
confidence: 99%